2007
DOI: 10.4265/bio.12.93
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Action of Didecyldimethylammonium chloride (DDAC) against Escherichia coli and Morphological Changes of the Cells

Abstract: The antibacterial activity of a disinfectant with geminated twin long-chain alkyl groups, didecyldimethylammonium chloride (DDAC), was investigated.The minimum inhibitory concentration (MIC) value of DDAC against Eschrichia coil was revealed to be a small value, 1.3 mg/L, by using the specific growth rates, IA, obtained from the cultivation in a liquid nutrient broth (NB) medium. The relationship between the leakage of proteins or 13 -galactosidase and the DDAC concentration showed that the leakage of intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 11 publications
4
31
0
Order By: Relevance
“…However, the growth and proliferation of adherent bacteria can be inhibited by the cured adhesive with cationic moieties, as suggested in a previous study with MDPB-containing material (Imazato et al, 2003b). Unlike the soluble polycationic agents, presumably exerting biocidal activity (Sumitomo et al, 2006;Yoshimatsu and Hiyama, 2007), the immobilized cationic biocide was reported to be bacteriostatic (Ebi et al, 2001;Imazato et al, 2003b). This attenuated antibacterial effect might exert influence on the physiological status and the membrane configuration of bacteria, leading to retarded bacterial proliferation and biofilm initiation.…”
Section: Discussionmentioning
confidence: 74%
“…However, the growth and proliferation of adherent bacteria can be inhibited by the cured adhesive with cationic moieties, as suggested in a previous study with MDPB-containing material (Imazato et al, 2003b). Unlike the soluble polycationic agents, presumably exerting biocidal activity (Sumitomo et al, 2006;Yoshimatsu and Hiyama, 2007), the immobilized cationic biocide was reported to be bacteriostatic (Ebi et al, 2001;Imazato et al, 2003b). This attenuated antibacterial effect might exert influence on the physiological status and the membrane configuration of bacteria, leading to retarded bacterial proliferation and biofilm initiation.…”
Section: Discussionmentioning
confidence: 74%
“…17,18 However, there are reports in the literature describing that monomers incorporated into composite resins lose their bactericidal activity compared to their water-soluble forms. 12,19 Whether this attenuated antibacterial effect of immobilized monomer is strong enough to interrupt the integrity of bacterial membrane and then trigger the efflux of cytoplasmic constituents remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…This process may contribute to the disruption of cell membranes, and subsequently lead to the increase of cell permeability and the leakage of the cytoplasmatic constituents. 17,18 As for the immobilized cationic biocide, hitherto, the antibacterial efficiency and the underlying antibacterial mechanism are still controversial in the literature. MDPBcontaining resinous materials were reported to exhibit bacteriostatic effect in stead of bactericidal effect.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that DDAC might improve membrane lipid integrity in a variety of cells. DDAC kills bacterial cells 5 min after treatment; autolysis is initiated in cells due to the breakdown of both RNA materials and highly ordered membranes, which coincides with potassium depletion and the leakage of proteins and β-galactosidase from cells (Ioannou et al, 2007;Yoshimatsu and Hiyama, 2007). Furthermore, P. fluorescens degrade DDAC to produce dimethylamine (Nishihara et al, 2000), which is particularly toxic to the respiratory systems of rats and mice (Coon et al, 1970;Buckley et al, 1985).…”
Section: Discussionmentioning
confidence: 98%